The monuments of the borderline village of Choratan and the results of the excavations of Saint Hripsime church - Nalbandyan, Arman (History and Culture, 2025)
The village of Choratan of the Tavush Province of RA, is located 90 km from the provincial capital, 22 km southeast of the city of Berd, on the southeastern slope of the Khndzorut mountain range. Мodern Choratan was formed by 12 families who arrived from Artsakh in the mid-18th century. Since then, the village has undergone several emigrations (in the 1770s, 1800s, 1850s), and part of the population was resettled to other settlements. In the 1830s, the village was one of the largest communities in the region. However, the history of the village’s activity as a medieval settlement has much deeper roots, which is clearly evidenced by a number of medieval monuments preserved on its administrative territory. And the fact that the community had its own spiritual and educational center in the Middle Ages is evidenced by Saint Hripsime Church in the center of the village. The church, as we’ll see, has close connections with one of the largest spiritual centers in the region_Khoranashat Monastery. As part of the restoration project of the church by local benefactors, the expedition of the Scientific Research Center of Historical and Cultural Heritage (the expedition leader_ A. Nalbandyan) conducted archaeological research and excavations of the site in 2016 and 2019. Excavations not only gave important results from the point of view of archeology and epigraphy, but also clarified the issue of the architectural structure of the church.